If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(4n + -8) = -8 Reorder the terms: 8 + -1(-8 + 4n) = -8 8 + (-8 * -1 + 4n * -1) = -8 8 + (8 + -4n) = -8 Combine like terms: 8 + 8 = 16 16 + -4n = -8 Solving 16 + -4n = -8 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -4n = -8 + -16 Combine like terms: 16 + -16 = 0 0 + -4n = -8 + -16 -4n = -8 + -16 Combine like terms: -8 + -16 = -24 -4n = -24 Divide each side by '-4'. n = 6 Simplifying n = 6
| 2(x-1)=3x-7 | | 25-2x=15 | | 1.8x-8=22 | | 2x-(-4)=96+(-10) | | 3x+4y=9.4 | | 4z/6-6=5 | | d/12-6=1 | | -8x+2=74 | | 6=-3+v | | -18a/6 | | 3x+4x=9.4 | | f(x)=3x^4-13x^2+14 | | 1.8q-5.4-1.7q=-0.9q-5.1 | | 2(5c-5.1)=-20.1 | | 128=-t^2+6t | | 22+7=3(22)-3 | | 2(x+3)=x+5+x | | 2(3x+1)=10x-6 | | Rx+sy=16 | | 4+14p-1=8p+87-6p | | 9x+18=6x+21 | | 2p+1=p+3 | | t^2-6t+128=0 | | 2(2)-3=0 | | 6x^2-24x-72=32 | | (4x)(2)=(3x)(243) | | 4+-4p=16 | | 2x-12=x+32 | | 3k=34 | | 6x-10x+4=-2x | | 11r=40-9r | | 5x+1=3x+16 |